Pediatric erythroblastic sarcoma/pure erythroid leukemia with NFIA-CBFA2T3 translocation: Report of two cases, including a case with TP53 mutation, and review of the literature - Cardoni, Antonello; Rogges, Evelina; Rossi, Sabrina; Vito, Rita De; Rullo, Emma; Vallese, Silvia; Barresi, Sabina; Giovannoni, Isabella; Tancredi, Chantal; Alesi, Viola; Coulomb, Aurore; Ceolin, Valeria; et al. (Human Pathology Reports, 2025)
Pure erythroid leukemia is a rare neoplasm that occurs predominantly in adults, mostly as secondary to cytotoxic chemotherapy and frequently with biallelicTP53abnormalities. Reports in pediatric patients are even rarer and show neoplasm arising “de novo”, frequent extramedullary sarcomatous presentation and a different molecular profile from the adult counterpart, including frequent gene fusions and no evidence of biallelic TP53 alterations. We describe two cases of pediatric erythroid leukemia / sarcoma with the NFIA::CBFA2T3 fusion, one of which harbored a TP53 mutation,with a review of the literature of pediatric cases with the same fusion and with the analogous NFIA::CBFA2T1 fusion.